APOS analysis on cognitive process in mathematical proving activities - Syamsuri Syamsuri; Indiana Marethi (International Journal on Teaching and Learning Mathematics, 2018)
Thinking is very necessary in learning mathematics, both at school and college level. Several studies have attempted to reveal students' thinking in learning mathematics at college. This article aims to describe the mental structure that occurs when constructing mathematical proofs in terms of APOS theory. The APOS theory has been widely used in analyzing the formation of mathematical concepts in universities. This research explores a thinking process in proof constructing. It uses a qualitative approach. The research was conducted on 26 students majored in mathematics education in public university at Banten, Indonesia. The consideration of that was because the students were able to think a formal proof in mathematics. Results show that there are two types of thinking process in mathematical proving activities, namely:  the deductive-holistic and the inductive-partial type of thinking process. Based on the results, some suitable learning activities should be designed to support the construction of these mental categories.